(untitled) (Justicia &Derecho, 2021)
The increasing application of artificial intelligence in our day to day, highlights the extraordinary development of this technology. Thus, today we can observe the use of the intelligence artificial for the assistance and execution of tasks of the most diverse nature, including the legal field. There are already in use different programs or platforms nurtured with information of legal interest that allows solving legal cases in a short time. The latter raises the possibility of going one step further and incorporating robot judges for the administration of justice, which raises as many concerns as expectations, issues that this research analyze.